Media Portrayal of Voluntary Public Reporting About Corporate Social Responsibility Performance: Does Coverage Encourage or Discourage Ethical Management? - Dickson, Marsha A. (Journal of business ethics, 2008)
Drawing on constructionist theory, this study examines how the media portrayed five public reporting events initiated by the Fair Labor Association (FLA), considering whether the coverage encourages or discourages companies from undertaking a reporting initiative as part of their ethical management. Media coverage was limited but generally favorable across all five events. Coverage frequently included claims made by FLA spokespersons and provided basic facts about the organization and its activities. Extensive detail about labor violations found by monitors was often included. Additional media coverage centered around themes of public reporting and transparency, an assessment of the FLA’s work, brand accountability and responsibility of corporations with regard to working conditions and labor standards, and specifics about the factory monitoring and partnering with factories and NGOs that is necessary to achieve change. Counter-claims brought question to the FLA’s efforts. Explanations about why the social condition exists were fairly limited, and thus, provided little insight into how the problems might be resolved. We discuss managerial implications regarding public reporting initiatives and media coverage, particularly regarding the countering effects of positive coverage and diminishing news stories.